Sweat feeding behavior by the Moth Arthroschista hilaralis (Crambidae) in the Maliau Basin conservation area (Sabah, Borneo) - Kenji Suetsugu; Monica Suleiman; Hirokazu Tsukaya (The American Entomological Society, 2018)
The feeding habits of adult lepidopterans are both incredibly diverse and poorly understood (Adler, 1982). In general, the diets of such adults are less specific and more opportunistic than those of lepidopteran larvae. In addition to floral and extrafloral nectar, adults have been reported to utilize an extensive variety of food sources including dung, urine, the crushed bodies of conspecifics, mud puddles, soil, carrion, lachrymal secretions, moist campfire ashes, saliva, soap suds, plain salt, blood, aphid honeydew, frog-hopper larval secretions, the nectar gland secretion of lycaenid larvae, fermented milk, fruits, seeds, tree sap, honey, and red wine (Adler, 1982).